Luís Antonio Cajazeira Ramos: um sísifo absurdo na poesia contemporânea - Oliveira, Luciana Santos de (2010)
The aim of this work is to analyze the lyric production of Luís Antonio Cajazeira Ramos from the perspective of the post-modern context considering that this author brings into his poetic writing the sensitive perception of the events which mark our contemporaneity. This thesis analyzes what prompts the poetic production nowadays, pointing to its characteristics as well to what particularizes, both culturally and historically, post-modernity. Furthermore, it tackles the condition of the poet and of contemporary poetry, which, besides representing a highly shattered world – a modern heritage –, faces the challenge of telling the experiences allowed by actualities without following modernist models that are part of a tradition. Therefore, the poetics of Cajazeira Ramos points to some possibilities for contemporary poetry to continue to exist in its place of displacement and to continue following in the representation of the post-modern atmosphere. And the main possibility is to receive and accept, in its lyric poetry, the consciousness of the absurd as the only possibly condition.